2021
DOI: 10.1134/s1547477121020072
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Oral Administration of Silver Nanoparticles on Cognitive Abilities of Mice

Abstract: To assess the effect of silver nanoparticles on mice cognitive abilities, daily, up to 4-month period, experimental mice were administrated with silver nanoparticles solution. Accumulation of silver in brain was assessed by neutron activation analysis. Cognitive abilities in mice before and after silver nanoparticles administration were evaluated in the Morris water maze behavioral test. No significant differences in the amounts of silver accumulated in brain were found between capable and incapable animals. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Results from the MWM of the main test have statistically demonstrated no significant differences in parameters’ values among experimental groups compared to controls. So, it is concluded that Ag-NPs with a dosage of 13 mg/ml and size of 34 ± 1.4 nm in mice treated for 2 and 4 months do not affect spatial learning and memory [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results from the MWM of the main test have statistically demonstrated no significant differences in parameters’ values among experimental groups compared to controls. So, it is concluded that Ag-NPs with a dosage of 13 mg/ml and size of 34 ± 1.4 nm in mice treated for 2 and 4 months do not affect spatial learning and memory [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of spatial learning and memory. One cycle of testing (three days of primary learning) was performed in the Morris water maze (MWM), according to the early developed protocol of the testing [37,38] with additional assessment of the flexibility of developed spatial memory by subsequent re-positioning of the platform into the other part of the swimming pool (fourth day) [39]. The circular white pool (1.5 m in diameter) was filled with water, and various visible clues were positioned around the pool.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…For each animal was determined the behavioral type was demonstrated during trials in three days of primary learning. Similarly to the previously developed protocol [40], the general sample was divided into three groups, "incapable", "capable", and "intermediate" animals, based on the type of behavior most frequently shown on Day 3. Incapable mice were excluded from the MWM as being non-responsive to potential changes induced by AuNPs that could be detected in this test; they demonstrated types of behavior, which did not include exploration of the pool.…”
Section: Behavioral Testsmentioning
confidence: 99%